498 Saccharomyces Cerevisiae Supplementations Effect on Fiber Digestibility in Equine. (10th April 2018) - Nerlich, H K; Koler, R; Powell, E; Williams, T L
Abstract: Probiotics have become increasingly common in equine diets to aid in fermentation in the hindgut. Yeast culture additive, such as Saccharomyces cerevisiae, is a common probiotic that has recently been used to optimize equine diets by enhancing nutrient digestibility. Yeast culture has been shown to increase the activity of cellulolytic bacteria in the hindgut by stabilizing cecal pH, which maximizes fiber fermentation. Dietary energy, dry matter, crude protein, NDF, ADF, hemicellulose, and cellulose apparent digestibility also increased when yeast culture was supplemented. However, studies examining the effect of yeast culture additive have been conflicting and inconsistent. The objective of the current study was to investigate the effect of Saccharomyces cerevisiae supplementation on weight gain and nutrient digestibility, focusing on NDF and ADF levels in healthy horses. A live strain of Saccharomyces cerevisiae product was provided to twelve horses of varying age, breed, and weight. The current study utilized an 88 d switchback design sectioned into two 44 d trial periods, including a 14 d adjustment period. Horses were randomly sectioned into two groups; supplemented then control, or control then supplemented. Horses were supplemented at a rate of 1 ounce twice daily with feed, at 0730 and 1700, as suggested by the product. Body weights were recorded weekly and a biweekly fecal grab sample was collected from each horse. Fecal samples were frozen at -80⁰C and then dried for 36 hours in a 70⁰C oven. Samples were sent to Cumberland Valley Labs for analysis of ADF, NDF, and ADL, using ADL as an internal marker. Weight and digestibility analysis was done using LSM in Proc GLM through SAS 9.0. There was no significant change in weight (P>.05) due to yeast supplementation. Apparent NDF digestibility was not effected by treatment (P=.296), while apparent ADF digestibility was increased due to supplementation (P<.0001). Overall, Saccharomyces cerevisiae, as supplemented in the current study, increased ADF, but did not increase NDF or cause a change in weight. An increase in ADF correlates to an increase in forage digestibility, enhancing overall equine gut health.